2013
DOI: 10.5248/122.73
|View full text |Cite
|
Sign up to set email alerts
|

Tuber sinoaestivum sp. nov., an edible truffle from southwestern China

Abstract: A new Tuber species, T. sinoaestivum, is described from southwestern China based on morphological and molecular analyses. The new species, which was found fruiting in association with Pinus armandii, has been previously misidentified as T. aestivum (=T. uncinatum). Although morphologically quite similar, T. sinoaestivum differs from the European species by more globose ascospores ornamented with a shallower reticulum. ITS sequence analyses show only 92% similarity between the two species, further supporting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…Tuberaceae, which include the edible ectomycorrhizal fungi known as truffles, is a family of great economic importance (Percudani et al., 1999). At least ten new species have been described by KIB taxonomists for the genus Tuber , namely, Tuber badium S. P. Wan, Tuber depressum S. P. Wan, Tuber verrucosivolvum S. P. Wan, Tuber sinoaestivum J. P. Zhang & P. G. Liu, Tuber panzhihuanense X. J. Deng & Y. Wang, Tuber sinoniveum S. P. Wan & F. Q. Yu, Tuber shidianense S. P. Wan, Tuber calosporum S. P. Wan, Tuber polymorphosporum S. P. Wan, and Tuber baoshanense S. P. Wan (Deng et al., 2013b, Wan et al., 2016, Wan et al., 2017a, Wan et al., 2017b, Xu et al., 2017, Zhang et al., 2012a). Additionally, one new species, Choiromyces helanshanensis Juan Chen & P.G.…”
Section: Progress Of Taxonomy At Kibmentioning
confidence: 99%
“…Tuberaceae, which include the edible ectomycorrhizal fungi known as truffles, is a family of great economic importance (Percudani et al., 1999). At least ten new species have been described by KIB taxonomists for the genus Tuber , namely, Tuber badium S. P. Wan, Tuber depressum S. P. Wan, Tuber verrucosivolvum S. P. Wan, Tuber sinoaestivum J. P. Zhang & P. G. Liu, Tuber panzhihuanense X. J. Deng & Y. Wang, Tuber sinoniveum S. P. Wan & F. Q. Yu, Tuber shidianense S. P. Wan, Tuber calosporum S. P. Wan, Tuber polymorphosporum S. P. Wan, and Tuber baoshanense S. P. Wan (Deng et al., 2013b, Wan et al., 2016, Wan et al., 2017a, Wan et al., 2017b, Xu et al., 2017, Zhang et al., 2012a). Additionally, one new species, Choiromyces helanshanensis Juan Chen & P.G.…”
Section: Progress Of Taxonomy At Kibmentioning
confidence: 99%
“…Although the Chinese species Tuber sinoestivum J. P. Zhang & P.G. Liu (Zhang et al, 2012) has not yet been found to contaminate T. aestivum inoculated plants in Europe, there is the ever present risk that this species will find its way onto European plants either through the accidental or deliberate mixing of its spores with T. aestivum in inocula . To reduce the risks of having contaminated inocula used to produce Tuber mycorrhized plants, truffles can be screened and incorrect species removed prior to the production of inocula.…”
Section: Ecological Studiesmentioning
confidence: 99%
“…pseudoexcavatum [20] . T. indicum complex是由一类形态上高度相似, 但分子系统 学上属明显不同分支的2~4个隐形种组成 [22,23] , 包括 T. liaodongense等6种块菌 [25,26] 及子囊孢子表面网纹的深度 [8] .…”
Section: 结果与分析unclassified
“…indicum complex)以及假凹陷块菌(T. pseudoexcavatum Y. Wang, G. Moreno, Riousset, Manjón & G. Riousset) [7] 和中华夏块菌(T. sinoastivum J.P. Zhang & P.G. Liu) [8] . 酰胺及芳香性化合物等多种生物活性物质, 其具有增 强免疫力、抗衰老、抗肿瘤、止血调节女性月经周 期和性功能等作用 [9] .…”
unclassified